Tax compliance for sustainable development by private health practitioners in Malaysia / Norlaila Md Zin … [et al.] - Md Zin, Norlaila; Arifin, Noratikah; Kasim, Eley Suzana; Mohd Saudi, Mohd Haizam; Ismail, Isyahira (Universiti Teknologi MARA, 2021)
Tax non-compliance leads to tax evasion and low tax collection, which ultimately may hamper the achievement of Sustainable Development Goals (SDGs). Prior studies suggest that tax compliance is influenced by taxpayers’ attitude, quality of public governance and cost of tax compliance. However, studies that focus on tax compliance among health practitioners are still sparse. Given that potential tax evasion among private health practitioners may lead to a significant loss in government revenue, this study aimed to examine the factors influencing tax compliance among private health practitioners. Data was gathered through a survey involving 271 health practitioners in Malaysia. The findings indicated that only the quality of public governance had a significant relationship with tax compliance while attitude of taxpayers and cost of tax compliance did not significantly influence tax compliance among private health practitioners. This study contributes to the body of knowledge by providing current evidence of tax compliance among health practitioners. By highlighting the importance of educating health practitioners on tax compliance, the study also provides guidance to regulators in planning for more effective tax education and awareness programs.